The Association Between Preoperative Physical Activity and Postoperative Surgical Outcomes and Survival Following Pelvic Exenteration - Patrick Campbell; Michael Solomon; Cherry Koh; Peter Lee; Kirk Austin; Lilian Whitehead; Neil Pillinger; Sascha Karunaratne; Daniel Steffens (Gastrointestinal Disorders)
Introduction: Pelvic cancers present significant health challenges and often require aggressive treatment strategies. Pelvic exenteration, which involves the resection of multiple pelvic organs, is currently the only curative option for advanced or recurrent pelvic malignancies. Due to its extensive nature, it carries a high risk for postoperative complications and extended hospital stays. Current evidence suggest that improved preoperative fitness is associated with better postoperative outcomes. This study explored the relationship between preoperative self-reported physical activity levels and surgical outcomes following pelvic exenteration. Methods: This retrospective cohort study included consecutive adult patients undergoing pelvic exenteration at Royal Prince Alfred Hospital between May 2017 and December 2023. Eligible participants completed the International Physical Activity Questionnaire—Short Form (IPAQ-SF) preoperatively. Primary outcomes included postoperative morbidity, length of hospital stay, and survival. Univariate and multivariate logistic regression analyses explored the association between preoperative physical activity and postoperative outcomes. Results: A total of 256 participants were included, of which 115 (44.9%) were classified as active. Active patients experienced fewer postoperative complications (p = 0.047) and shorter hospital stays (p = 0.007), compared to inactive participants. There was no significant association between preoperative physical activity levels and survival outcomes (p = 0.749). Younger age, preoperative physical activity level, and advanced primary malignancy were significantly associated with fewer complications and shorter hospital stays. Conclusions: Higher levels of preoperative physical activity is associated with fewer postoperative complications and shorter hospital stays in patients undergoing pelvic exenteration. These findings support the potential benefits of incorporating prehabilitation programs to improve surgical outcomes and reduce healthcare costs.